A systematic study on composition and antioxidant of 15 varieties of wild Idesia polycarpa fruits in China - Xiaoni Guo; Qiang Zhang; Yaobing Chen; Xiufang Huang; Wenqing Yang; Song Li; Shunyao Li; Kai Luo; Xiulan Xin (Frontiers in Sustainable Food Systems, 2023)
Idesia polycarpa is a good source of high-quality vegetable oil and can potentially alleviate pressure on the supply of edible oil. Exploring Idesia polycarpa could enrich the world’s food and oil resources and make up for the shortage of vegetable oil types and production. Here, 15 varieties of wild Idesia polycarpa from major wild Idesia polycarpa resource belts in the middle and upper reaches of the Yangtze River in China were investigated to elucidate the quality and antioxidant activity of wild Idesia polycarpa fruits to tap the potential exploitation capacity of Idesia polycarpa. In this study, wild Idesia polycarpa varieties with high oil quality and antioxidant activity were screened by the comprehensive evaluation of 42 indexes including oil content, dry basis white grain weight, fatty acids, tocopherols, total flavonoids, and minerals, as well as comparisons of free radical scavenging of 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS)) and 1,1-diphenyl-2-picrylhydrazyl (DPPH). The result showed the quality characteristics of 15 wild Idesia polycarpa: oil (MN:29.21/100 g), dry basis white grain weight (MN:17.32 g), total flavonoids (MN:27.27 RE/kg), total polyphenols (MN:159.63 GAE/kg), tocopherols [MN:356.10 mg/kg (α-tocopherol (MN:284.96 mg/kg), γ-tocopherol (MN:50. 20 mg/kg), β-tocopherol (MN:9.54 mg/kg), and δ-tocopherol (MN:11.40 mg/kg)], total mineral content (MN:25653.44 mg/kg), and fatty acids [MN:20.89/100 g (70.42% polyunsaturated fatty acids (MN:14.63/100 g), 20.29% saturated fatty acids (MN:4.25/100 g), and 9.29% monounsaturated fatty acids (MN:2.01/100 g)]. Correlation analysis revealed that flavonoids, C16:0, C18:1n9c, C18:2n6c, polyphenols, α-tocopherol, δ-tocopherol, and Ca were significantly correlated with DPPH and ABTS. Cluster analysis and principal component analysis classified the 15 wild samples into three clusters, with the first cluster represented by H8, H6, and H9 being the optimal sample as a woody oilseed crop, the second cluster represented by H10, H 12, and H11 being the optimal sample for functional oil development, and the rest could be selected with emphasis when conducting certain characteristic product development. The excellent lipids and rich nutritional and antioxidant properties suggest that Idesia polycarpa will be a new direction for the development of edible oil resources in the future.